PENGEMBANGAN MODEL PEMBELAJARAN MENTAL SPIRITUAL UNTUK MENINGKATKAN MORAL KERJA PESERTA LEMBAGA KURSUS PERHOTELAN : Studi di LPT Panghegar Kota Bandung - Nasrudin, Ayi (2010)
The background of this research is the existence of objective conditions on the mental-spiritual learning model to improve morale at the agency course participants hospitality courses are inadequate, especially to produce graduates who have high morale. Hence the focus of this research is the development of mental-spiritual learning model to improve morale at the agency course participants hospitality courses. The objective is to develop models of learning that can improve the mental-spiritual morale course participants at the institute hospitality courses that can be implemented well. There are several theoretical foundation which are used in the research, such as: Training or learning theory at nonformal education from Djudju Sudjana, Learning model from Bruce Joyce, Marsha Weil, and Emily Calhoun, Abdul Azis Wahab, M. Djawad Dahlan, and the contextually theories. This research is a qualitative research method of research and development or research & development (R & D). To measure the effectiveness of the testing system through experiments. Collection of necessary data is done through questionnaires, interviews, observation, discussion and documentation study. Further data obtained are processed, analyzed qualitatively and equipped by the statistical tests to determine the significance of enhancing the effectiveness, then the overall results obtained by data collection, processing until the interpretation of data compiled and presented in the form of a dissertation. The findings of this research is to obtain a series of activities that are more ideal in the context of mental-spiritual learning to improve morale at the agency course participants hospitality courses. It tersbut is the result of the development of objective conditions that exist today. The conclusion of this research is that this study can achieve its intended purpose of preparing and developing the spiritual mental learning models to improve morale at the agency course participants effective hospitality courses to be implemented in the institution of the course. Achieving that goal is obtained through a series of research and development activities that lead to the drafting of the operational model of mental-spiritual learning to improve morale at the agency course participants hospitality courses are equipped with various conceptions infra and supra-structure of learning such as: curriculum and planning aspects of other training. Latar belakang penelitian ini adalah adanya kondisi obyektif tentang model pembelajaran mental spiritual untuk meningkatkan moral kerja peserta kursus di lembaga kursus perhotelan yang kurang memadai, trutama untuk menghasilkan lulusan yang memiliki moral kerja yang tinggi. Karenanya fokus penelitian ini ialah mengenai pengembangan model pembelajaran mental spiritual untuk meningkatkan moral kerja peserta kursus di lembaga kursus perhotelan. Adapun tujuannya ialah untuk menyusun model pembelajaran mental spiritual yang dapat meningkatkan moral kerja peserta kursus di lembaga kursus perhotelan yang dapat diimplementasikan dengan baik. Beberapa teori yang digunakan dalam penelitian ini, di antaranya; Teori pelatihan dan pembelajaran pendidikan nonformal dari Djudju Sudjana, Model pembelajaran dari Bruce Joyce, Marsha Weil, dan Emily Calhoun, Abdul Azis Wahab, M. Djawad Dahlan serta teori terkait lainnya. Penelitian ini merupakan penelitian kualitatif dengan metode penelitian dan pengembangan atau research & development (R & D). Untuk mengukur efektifitas dalam uji coba sistem dilakukan melalui eksperimen. Pengumpulan data yang dibutuhkan dilakukan melalui kuisioner, wawancara, observasi, diskusi dan studi dokumentasi. Selanjutnya data yang diperoleh diolah, dianalisis secara kualitatif dan dilengkapi oleh uji statistik untuk mengetahui adanya signifikansi peningkatan efektifitas, kemudian keseluruhan hasil pengumpulan data yang diperoleh, pengolahan sampai interpretasi data disusun dan disajikan dalam bentuk disertasi. Temuan penelitian ini adalah diperolehnya rangkaian kegiatan yang lebih ideal dalam rangka pembelajaran mental spiritual untuk meningkatkan moral kerja peserta kursus di lembaga kursus perhotelan. Hal tersebut merupakan hasil pengembangan dari kondisi obyekyif yang ada sekarang ini. Kesimpulan dari penelitian ini adalah bahwa penelitian ini dapat mencapai tujuan yang telah ditetapkan yaitu menyusun serta mengembangkan model pembelajaran mental spiritual untuk meningkatkan moral kerja peserta kursus di lembaga kursus perhotelan yang efektif untuk diimplementasikan di lembaga kursus. Pencapaian tujuan tersebut diperoleh melalui rangkaian kegiatan oenelitian dan pengembangan yang secara operasional bermuara pada tersusunnya model pembelajaran mental spiritual untuk meningkatkan moral kerja peserta kursus di lembaga kursus perhotelan yang dilengkapi dengan berbagai konsepsi infra dan supra-struktur pembelajaran seperti: kurikulum serta aspek-aspek perencanaan kegiatan pelatihan lainnya. ABSTRACT The background of this research is the existence of objective conditions on the mental-spiritual learning model to improve morale at the agency course participants hospitality courses are inadequate, especially to produce graduates who have high morale. Hence the focus of this research is the development of mental-spiritual learning model to improve morale at the agency course participants hospitality courses. The objective is to develop models of learning that can improve the mental-spiritual morale course participants at the institute hospitality courses that can be implemented well. There are several theoretical foundation which are used in the research, such as: Training or learning theory at nonformal education from Djudju Sudjana, Learning model from Bruce Joyce, Marsha Weil, and Emily Calhoun, Abdul Azis Wahab, M. Djawad Dahlan, and the contextually theories. This research is a qualitative research method of research and development or research & development (R & D). To measure the effectiveness of the testing system through experiments. Collection of necessary data is done through questionnaires, interviews, observation, discussion and documentation study. Further data obtained are processed, analyzed qualitatively and equipped by the statistical tests to determine the significance of enhancing the effectiveness, then the overall results obtained by data collection, processing until the interpretation of data compiled and presented in the form of a dissertation. The findings of this research is to obtain a series of activities that are more ideal in the context of mental-spiritual learning to improve morale at the agency course participants hospitality courses. It tersbut is the result of the development of objective conditions that exist today. The conclusion of this research is that this study can achieve its intended purpose of preparing and developing the spiritual mental learning models to improve morale at the agency course participants effective hospitality courses to be implemented in the institution of the course. Achieving that goal is obtained through a series of research and development activities that lead to the drafting of the operational model of mental-spiritual learning to improve morale at the agency course participants hospitality courses are equipped with various conceptions infra and supra-structure of learning such as: curriculum and planning aspects of other training.